In Vivo Cell Fusion between Mesenchymal Stroma/Stem-Like Cells and Breast Cancer Cells - Melzer, Catharina (Cancers (Basel), 2019)
Cellular communication within the tumor microenvironment enables important interactions between cancer cells and recruited adjacent populations including mesenchymal stroma/stem-like cells (MSC). These interactions were monitored in vivo following co-injection of GFP-labeled human MSC together with mcherry-labeled MDA-MB-231 breast cancer cells in NODscid mice. Within 14 days of tumor development the number of initially co-injected MSC had significantly declined and spontaneous formation of breast cancer/MSC hybrid cells was observed by the appearance of double fluorescing cells. This in vivo fusion displayed a rare event and occurred in less than 0.5% of the tumor cell population. Similar findings were observed in a parallel in vitro co-culture. Characterization of the new cell fusion products obtained after two consecutive flow cytometry cell sorting and single cell cloning revealed two populations, termed MDA-hyb3 and MDA-hyb4. The breast cancer fusion cells expressed both, GFP and mcherry and displayed more characteristics of the MDA-MB-231 cells than of the parental MSC. While little if any differences were determined in the proliferative capacity, a significant delay of MDA-hyb3 cells in tumor formation was observed when compared to the parental MDA-MB-231 cells. Moreover, MDA-hyb3 cells developed an altered pattern of distant organ metastases. These findings demonstrated dynamic tumor changes by in vivo and in vitro fusion with the development of new breast cancer hybrid cells carrying altered tumorigenic properties. Consequently, cancer cell fusion contributes to progressively increasing tumor heterogeneity which complicates a therapeutic regimen.